Development of mathematics teaching material based on numeracy for blended learning - Hapizah Hapizah; Budi Mulyono; Ely Susanti; Gresilia Situmorang; M. David Safitra; Amieyah Nuradinda; Norulhuda Ismail (Sriwijaya University Learning and Education International Journal, 2024)
Technology-assisted learning positively improves students' abilities, one of which is blended learning, which combines synchronous learning and asynchronous learning. The article discusses research that aims to produce numeration-based mathematics teaching materials for blended learning that are valid, practical, and potentially affect students' numeracy skills in class VII. This research is development research with preliminary and formative evaluation stages. The subjects in this study were 30 students of class VII E, at one of the Public Middle Schools in Palembang City. Data was collected through questionnaires, tests, and interviews. The results of the study stated that the numeration-based mathematics teaching materials for blended learning were in the valid category with a score of 85 and in the practical category with a score of 92 and had a potential effect on the numeracy abilities of class VII students with an average score of 77 in the good category. In addition, the results of this study indicate that students' responses to teaching materials are in a good category.